Wastewater treatment on soils of low permeability : interim report - Hoeppel, Ronald E; Waterways Experiment Station (U.S.) (Vicksburg : U.S. Army, Engineer Waterways Experiment Station, Office for Environmental Studies, 1974)
Sponsored by U.S. Army Cold Regions Research and Engineering Laboratory, Hanover, N.H., and Office, Chief of Engineers, U.S. Army. Bibliography: p. 80-84. Mode of access: Internet.